The Influence of Co-curricular and Extracurricular Program Management of Al-Qur'an Memorization on the Dimensions of Graduate Profiles - Elvarisna Elvarisna; M. Haviz; Dona Afriyani (Journal of Education Research, 2026)
This study investigates the systemic shortfall in achieving graduate profile dimensions, particularly regarding character-based competencies such as faith, ethical conduct, and independence. It evaluates the strategic influence of co-curricular management and extracurricular Quranic memorization programs in bridging these developmental gaps within public junior high schools in Sijunjung District. Employing a quantitative correlational framework, data were elicited from 103 teachers selected through stratified random sampling ($N = 140$). The analytical path involved rigorous validity and reliability testing, followed by simple and multiple linear regression models.The findings reveal that: (1) structured co-curricular management significantly enhances the graduate profile, accounting for a 35–45% variance in its development; (2) extracurricular Quranic programs contribute 30–40% to character outcomes; and (3) the integrated management of both variables yields a synergistic effect, explaining up to 65% of the total influence. These results suggest that character internalization is most effective when administrative planning and spiritual activities are inextricably linked within a sustainable school ecosystem. Practically, the study underscores the necessity for educational stakeholders to institutionalize integrated program evaluations to ensure student character development aligns with national standards.